2006
DOI: 10.1021/ma052571n
|View full text |Cite
|
Sign up to set email alerts
|

Study of Morphologies of PMMA/PP/PS Ternary Blends

Abstract: In this work, the morphologies of PMMA/PP/PS blends of different concentrations were studied and compared to the predictions of spreading coefficient, minimum free energy, and dynamic interfacial energy phenomenological models. Different morphologies than the ones predicted by the phenomenological models were observed in the case of PMMA matrix: a mixture of core-shell morphology (core of PP and shell of PS), dispersed PS, and subinclusions within the core when the concentration of PP was increased were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 35 publications
9
131
1
Order By: Relevance
“…The predicted morphologies by interfacial free energy model corroborated the morphologies experimentally as shown in Table 1. The most stable morphology is represented by the lowest value of surface energy of Gibbs energy of mixing [14]. Figure 3 shows the SEM micrographs of blend morphologies of the samples before and after solvent etching prepared by injection molding.…”
Section: Results and Discussion Blend Morphology Characterizationmentioning
confidence: 99%
“…The predicted morphologies by interfacial free energy model corroborated the morphologies experimentally as shown in Table 1. The most stable morphology is represented by the lowest value of surface energy of Gibbs energy of mixing [14]. Figure 3 shows the SEM micrographs of blend morphologies of the samples before and after solvent etching prepared by injection molding.…”
Section: Results and Discussion Blend Morphology Characterizationmentioning
confidence: 99%
“…For any type of morphology the free energy of mixing can be written as Equation (5): (5) where μ i is the chemical potential of i, n i is the number of moles of i, A ij is the interfacial area between components i and j and γ ij is the interfacial tension between components i and j. The lowest value of (∑A ij γ ij ) will correspond to the lowest value of Gibbs morphology [3,7,8,[36][37][38]. Accordingly, the morphology of multiphase systems can be controlled through changing the interfacial interaction between the blend components [39].…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Obviously, the degree of success to achieve such polymer blends with prescribed properties is strongly influenced by their interfacial interaction. Therefore understanding the role of parameters which control the morphology development of the blends has become important issue for both academic researchers and manufacturers [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…12,14,17,[20][21][22] Vanoene et al 25 showed that in the dynamic flow conditions, the elasticity difference between the phases of binary blends can influence the interfacial tension value so that the interfacial tension would be completely different from that of the static flow conditions. When the matrix is more elastic than the disperse phase, dynamic interfacial tension is less than the static interfacial tension.…”
Section: Introductionmentioning
confidence: 99%
“…18,26 Yet some others observed the contrary 19 and also there are some reports claiming ineffectiveness of the ratio of viscosities on the morphology type. 15,[21][22] Reignier et al 15 showed that to investigate the effect of the viscosity ratio on the morphology, the viscosity ratio should be calculated in a constant shear stress rather than a constant shear rate; because the continuity of the shear stress is more in the droplet-matrix interface compared to the shear rate. PS/SBR/PE polymer blends containing components with different viscosity ratios were also studied by Luzinov et al 27 They assumed ''core to shell viscosity'' as a measure of the core diameter and ''shell to matrix viscosity'' as a measure of dispersed phase diameter.…”
Section: Introductionmentioning
confidence: 99%